Trade and industrial teacher-training programs for Negroes in the southern region - McLeod, Jeremiah W., author; Hinderman, Roy Aaron, 1900-, advisor; Britton, Russell K., committee member; Marshall, T. O., committee member; Henry, George F., committee member (Colorado State University. Libraries, 1944)
To view the abstract, please see the full text of the document.
Keywords: Industrial arts -- Study and teaching; African Americans -- Education; Teachers -- Training of; Technical education -- Southern States